"It is frustrating to not have control even though I know it's not legal!": A mixed-methods investigation on applications to prevent mobile phone use while driving. (March 2020) - Oviedo-Trespalacios, Oscar; Truelove, Verity; King, Mark
Highlights: Mobile phone applications to prevent distraction reduce phone use. Drivers completed diaries and a questionnaire. Diaries show reliability issues with the applications. Management of involuntary distraction needs to be improved. Abstract: Mobile phone distracted driving is a major risk factor for crashes. However, this behaviour has been increasing in recent years. Effective enforcement of mobile phone bans while driving faces several obstacles; as such, it is important to consider additional countermeasures. Applications designed to prevent distracted driving are a promising solution, yet more research is needed that examines their effectiveness in reducing dangerous phone use while driving behaviours. Additionally, these applications are voluntary in nature; therefore, an understanding of drivers' perceptions of the applications is necessary to determine how to improve uptake. A mixed methods design was utilised to examine these factors in a comprehensive manner. A total of 40 participants used the smartphone application "Do Not Disturb While Driving" for iOS phone operating systems or "Android Auto" for Android phone operating systems for approximately one week and completed three diary entries reporting on their experience. Two questionnaires that examined phone use while driving behaviours were also administered to participants; one before and one after completing the study. The quantitative results found that engagement in 1) visual-manual, 2) cognitive-auditory and 3) music mobile phone interactions significantly decreased while using the application. Distraction engagement and mental workload while driving also significantly decreased while using the application. The qualitative results identified a number of areas of improvement that need to be addressed, e.g. activation of the application and Bluetooth connection reliability. The features that required improvement presented an obstacle for effective use of the applications, and in some cases resulted in drivers deciding to stop using the application. Positive perceptions of the application were associated with the experiences of the application functioning appropriately and activating automatically. These results show that applications designed for voluntary use to prevent mobile phone distracted driving are a promising countermeasure, although current applications require several improvements.